Construction and Design of the Dragon Trap in Insit Village, Tebing Tinggi Barat District, Kepulauan Meranti Regency, Riau - Silitonga, Ido Maruli; Nofrizal, Nofrizal; Yani, Alit Hindri (South East Asian Marine Sciences Journal, 2025)
This study aims to examine the construction and design of dragon traps used by fishermen in Insit Village, Tebing Tinggi Barat Sub-district, Meranti Islands Regency, Riau Province. Dragon traps are passive and environmentally friendly fishing gear that have only been used since 2022, primarily targeting shrimp, with bycatch including fish and crabs. The research was conducted over two weeks from August 26 to September 9, 2024, using survey and field observation methods. Data were collected through direct measurements of the fishing gear, interviews with fishermen, and visual documentation. The results showed that the dragon traps have a total length of 15 meters, with the main structure consisting of 36 galvanized iron frames. The trap body is made of polyethene (PE) netting with a mesh size of 0.5 inches, measuring 40 cm in length, 45 cm in width, and 30 cm in height. It has 32 entry holes (ijep) arranged alternately. Other components include two catch-holding chambers measuring 50 cm in length, 38 cm in width, and 25 cm in height, PE binding ropes, and 5-meter-long stakes. The fishing location is in shallow, muddy waters with a depth of 2–3 meters and approximately 150 meters from the shoreline. During the study, the dragon traps caught 120 kg of white shrimp (Penaeus merguiensis) out of a total catch of 149 kg. This indicates that the bubu naga is quite effective in capturing shrimp as its main target species.